Social background and its impact on the freedom of women within the Palestinian family: A field study applied to the residents of Qalqilya at the end of the second decade of the twentieth century - Alawneh, Abdelmajid Nayif (Journal of Humanities & Social Sciences, 2020)
The aim of this research is to know the extent of the impact of social background variables on the freedom of women within the Palestinian family from the viewpoint of all members of Palestinian society. The researcher used the descriptive analytical method and the questionnaire tool, and the research community is a resident of one of the Palestinian cities, which is the city of Qalqilya in the northern West Bank, A sample was taken of them amounting to (548) individuals from different groups, and it was found with regard to the private living areas that there is freedom for Palestinian women in them, as the total score for all of these areas came between the high and medium percentage, which reached a combined value of (73.7%) Distributed over The entire various fields in its existence ranged between (83.8%) for the existence of women’s freedom in the social field, followed by a value (5. 78%) for the existence of that freedom within the psychological field and (70.7%) came to the freedom of women within the democratic field The three domains represented the highest existence of women’s freedom in them, followed by the noticeable decrease in the existence of this freedom, which came with a value (9.67%) for the freedom of women in the practical behavioral field, followed by a percentage (4. 66%) of the existence of women’s freedom in the material field, and this means The practical, real presence of women’s freedom came in an average way compared to the theoretical existence, and it was found at the end of this research There is a strong relationship between the various variables of the social background and between the existence of women’s freedom within the Palestinian society, such as the existence of a relationship between gender, age, economic status, number of family members, the nature of work and the educational level and the existence of women’s freedom, and this means that there is a strong and significant impact of the changes in the social environment as a driver of existence Freedom of women in its apparent form between high and medium as it came in the areas mentioned in this research, and at the end of this research the researcher made a number of recommendations at the public and private levels, one of the most important of which was the need to give guidance courses for those coming to marriage to improve from a For the relations between the spouses and the creation of a kind of freedom in the beginning of the formation of any new family considering that this contributes to a decrease in some other social problems, in addition to the need to improve the treatment of women within every Palestinian family.